The December boys - Noonan, Michael (London: Catnip, 2007)
When a group of young boys leave the dusty outback orphanage where they've grown up for a summer at the coast, their future is full of possibilities. But the chance that one of them, just one, might gain a real family to live with calls everything they thought they knew about each other into question
Keywords: Young adult fiction